2020
DOI: 10.21325/jotags.2020.543
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Plate Waste on Menu Analysis

Abstract: In the study, it is aimed to determine the amount of plate waste and to use it with menu engineering (ME) method which is one of the most prevalent menu analysis approach in terms of literature and practices. A case study was conducted in a fine-dining restaurant in Antalya. In the study, 10 food items which are in the main course category on the dinner menu were taken into consideration. Material cost, sales amount and price data were collected through the document review while plate waste data was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It means that food good flavor positively influences food intake in patients, so the probability of waste logically became smaller. The type of vegetable dish that mostly became waste is the stir-fried vegetable dish 19 .…”
Section: Vegetable 4260mentioning
confidence: 99%
“…It means that food good flavor positively influences food intake in patients, so the probability of waste logically became smaller. The type of vegetable dish that mostly became waste is the stir-fried vegetable dish 19 .…”
Section: Vegetable 4260mentioning
confidence: 99%
“…For instance, food waste during the consumption phase can result from incorrect planning, changing consumer preferences, inappropriate materials or menus, and inadequate personnel performance (Ferreira et al 2013). The research conducted by Yiğitoğlu (2020) in a luxury restaurant business indicated that the amount of plate waste could be included in the menu analysis process as a variable that reflects the customer's opinion. Customers dissatisfied with their dining experience are expected to be more likely to leave waste on their plates.…”
Section: Introductionmentioning
confidence: 99%
“…So the Menu engineering system combining menu management with costing methods, can provide an important tool for achieving sustainable development of companies in the industry by compiling reports containing a detailed breakdown of the costs of each item on the menu (Linassi et al, 2016), menu engineering system helps managers make their decisions with reliable techniques and tools, as well as strives to produce the largest products with the least resources (de Souza Vianna et al, 2020). The menu is evaluated by the performance of the contents, where it contributed a great deal to analyzing food menus to determine performance, in addition, is easy to implement, simple, inexpensive, easy access to stock records, standard recipes, and costs used for food and beverages, as well as continuous development of menus which leads to good food and beverage management (Yiğitoğlu, 2020), also involves making adjustments on the placement order, classification or description of items included on food menus (Attwood et al, 2020). Menu engineering system in hotels provides information about useless added activities and get rid of waste, then delivered all cost information that encourages low-cost and high-quality product designs and target markets aids in make-or-buy decisions in a support kitchen and simplification suitable pricing strategies, which leads to staff grasp, the true benefits of a menu engineering system, they can perform tasks in a profitable manner, improving the business' sustainability (Raab and Zemke, 2016).…”
Section: Introductionmentioning
confidence: 99%